Symptoms of overtraining in resistance exercise: International cross-sectional survey - Grandou, C.; Wallace, L.; Coutts, A. J.; Bell, L.; Impellizzeri, F. M. (International Journal of Sports Physiology and Performance, 2021)
Purpose: To provide details on the nature and symptomatic profile of training maladaptation in competitive resistance-based athletes to examine whether there are symptoms that may be used as prognostic indicators of overtraining. Identifying prognostic tools to assess for training maladaptation is essential for avoiding severe overtraining conditions. Methods: A Web-based survey was distributed to a cross-sectional convenience sample of competitive athletes involved in sports with a significant resistance-training component. The 46-item anonymous survey was distributed via industry experts and social media from July to August 2019. Results: The final sample included 605 responses (completion rate: 84%). About 71% of the respondents indicated that they had previously experienced an unexplained decrease in performance. Among those, the majority reported a performance decrement lasting 1 wk to 1 mo (43.8%). General feelings of fatigue were the most frequent self-reported symptom of maladaptation. Acute training maladaptation, lasting <1 mo, was also accompanied by symptoms of musculoskeletal aches and pain. In the majority of cases (92.5%), training maladaptation was accompanied by additional nontraining stressors. A greater proportion of the respondents with more severe maladaptation (>4 mo) were training to muscle failure. Conclusion: The results from this study support the multifactorial nature of training maladaptation. The multidimensional nature of fatigue and individual variability in symptomatic responses precludes definitive prognostic symptoms or differential diagnostic factors of functional/nonfunctional overreaching or the overtraining syndrome in resistance exercise.